Identification of microorganisms by polymerase chain reaction in pulp necrosis and apical periodontitis - Leonardo Francisco López Arias; Purificación Varela Patiño; Rafael Seoane Prado; Benjamín Martin Biedma; José Domingo González Bahillo; Karen Rodríguez Pena (Editorial Ciencias Médicas, 2017)
Objectives: identify by polymerase chain reaction technique ten bacterial species obtained from necrotic root canals, and analyze their association with signs and symptoms of apical periodontitis (pain, exudate and mobility) in a specific geographic area: Santiago de Compostela (northwestern Spain). Methods: a descriptive study was conducted based on a one-year sample collection period. Forty-three samples were taken from necrotic root canals, at a rate of one sample per patient, who had been previously examined for radiographic apical periodontitis, of which the signs and symptoms were described. Sterile absorbent paper points were used to extract the DNA samples, applying the phenol-chloroform technique. The product was amplified by polymerase chain reaction, using specific primers for ten microorganisms. The result was visualized by electrophoresis using a UV transilluminator. Outcomes were analyzed statistically to determine which microorganisms were present individually and which formed associations such as the so-called red complex, according to the signs and symptoms present in the apical periodontitis. Results: Fusobacterium nucleatum was the most common individual microorganism (83.72 % of the samples). As to the association of microorganisms with signs and symptoms, Porphyromonas endodontalis was found to be significantly associated with exudate (p< 0.05) and mobility (p< 0.05), while both Enterococcus spp. and Treponema denticola (p< 0.01) had a significant association with pain. Incidence of the red complex was 6 cases in all. Conclusions: Fusobacterium nucleatum and Streptococcus spp. were the microorganisms identified as displaying the highest percentages. Porphyromonas endodontalis showed the greatest statistical association with signs and symptoms of apical periodontitis.